DETECTING FINANCIAL STATEMENT FRAUD IN STATE-OWNED ENTERPRISES: AN INTEGRATED ANALYSIS OF THE FRAUD HEXAGON AND BENEISH M-SCORE MODE - Muhammadiyah, Aisyiah Syamzami; Witjaksono, Armanto (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
This research analyzes the fraud hexagon in detecting financial statement fraud using the Beneish M-Score Model in State-Owned Enterprises (SOEs) during the period 2018-2022. Using secondary data from 20 companies listed on the Indonesia Stock Exchange, this study evaluates he impact of six fraud elements—pressure (proxied by financial targets, stability, and external pressure), opportunity, rationalization, capability, ego, and collusion—on fraudulent financial reporting. The findings indicate that the elements of Pressure in the Fraud Hexagon, proxied by financial targets, financial stability, and external pressure, significantly influence the detection of financial statement fraud, while other elements such as opportunity, rationalization, capability, ego, and collusion do not have a significant impact. This study provides crucial insights for SOEs to strengthen corporate governance systems and enhance internal audit functions to prevent financial statement fraud. The study contributes to fraud literature by integrating the Fraud Hexagon with the Beneish M-Score in an emerging market context and offers practical strategies for mitigating fraud risks in SOEs.